Recalling Masaryk's The Czech Question : Humanity and Politics on the Threshold of the Twenty-First Century - Svoboda, Jan, (Value Inquiry Book Series ;, 2023)
This book presents T. G. Masaryk's efforts to shape the identity of a small nation in late the 19th and early 20th century. It features contributions from leading Czech scholars who analyse Masaryk's efforts 120 years later. Masaryk is considered the most important figure in modern Czech history. Drawing on the ideas of his ideological predecessors and humanists, he wanted to integrate the Czech nation into the family of advanced world nations in line with international intellectual trends. Masaryk was the first in world history to fulfil the Platonic ideal of a philosopher who founded a state.